Popping My Collar: Applying Anthropology to the Field of Design and Marketing - Platz, Kayleigh Helene (University of Waterloo, 2009)
This paper explores the relationship between anthropological research methods and business, marketing and research design. It is based on participant observation and semi-structured interviews.
Keywords: Anthropological Methods; Business; Public Issues Anthropology